Peran Mahkamah Konstitusi Mencegah Gejala Autocratic Legalism di Indonesia - Miftah Faried Hadinatha (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
The phenomenon of autocratic legalism has become a serious problem that threatens democracy. As the guardian of constitution, the Constitutional Court should be present to stop the spread of this phenomenon. This research has two objectives, first, to understand the autocratic legalism phenomenon and the spread of it. Second, to formulate what kind of role the Constitutional Court can play to stop the escalation of it. The research methods used are doctrinal. The results showed, firstly, autocratic legalism refers to the actions of a person who uses the law to legitimize his desire for power. This can be seen in several policies issued in Indonesia. Second, the way the Constitutional Court can stop the escalation of it by adopting the doctrine of unconstitutional constitutional amendment and judicial activism in the exercise of judicial review.